Coated cutting tool
A coated cutting tool with controlled nitrogen content in the AlCrSi nitride hard coating, achieving improved durability and reduced brittleness by optimizing the B/A ratio and cubic crystal peak intensity, addresses durability issues in existing tools.
Patent Information
- Application Number
- JP2023103045
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
AI Technical Summary
Existing coated cutting tools with AlCrSi nitride hard coatings face durability issues due to uncontrollable nitrogen content ratios exceeding the specified upper limit, leading to increased residual compressive stress and potential self-destruction, limiting their application range and productivity.
A coated cutting tool with a hard coating composed of AlCrSi nitride or carbonitride, where the atomic ratio of metal elements to nitrogen (B/A) ranges from 1.07 to 1.30, with a peak intensity on the (200) or (111) plane of the cubic crystal, and minimal hexagonal AlN presence, ensuring excellent durability even with higher nitrogen content.
The solution provides a coated cutting tool with enhanced durability and reduced brittleness, suitable for a broader range of applications and improved productivity by minimizing hexagonal AlN and controlling nitrogen content within the specified atomic ratio.
Smart Images

Figure 2025002715000002 
Figure 2025002715000003 
Figure 2025002715000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated cutting tool. [Background technology]
[0002] AlCrSi nitride is a film type with excellent heat resistance and wear resistance, and is applied to coated cutting tools. The applicant of the present application has proposed to further increase the nitrogen content ratio of AlCrSi nitride hard coatings with a high Si content and fine structure (Patent Document 1). The hard coating described in Patent Document 1 has excellent wear resistance and can increase the durability of coated cutting tools in the milling of high-hardness steel. Patent Document 1 shows that if the nitrogen content ratio of the hard coating becomes too high, the residual compressive stress of the hard coating increases too much, making the hard coating more susceptible to self-destruction and reducing the durability of the tool. Therefore, Patent Document 1 sets the upper limit of B / A, which is the ratio of the atomic ratio A of metal elements to the atomic ratio B of nitrogen, to 1.07. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2015 / 141743 Summary of the Invention [Problem to be solved by the invention]
[0004] According to the inventors' investigations, it has been confirmed that, depending on the coating device, it is difficult to control the nitrogen contained in the hard coating, and the nitrogen content may become even higher than the upper limit value of B / A defined in Patent Document 1. If a coated cutting tool having excellent durability with a higher nitrogen content range than that of Patent Document 1 can be obtained, the range of application will be expanded and productivity will be increased. An object of the present invention is to provide a coated cutting tool having excellent durability even when the nitrogen content is high, using AlCrSi nitride having a high Si content and a fine structure. [Means for solving the problem]
[0005] (1) One aspect of the present invention is a coated cutting tool having a substrate and a hard coating on the substrate, the hard coating being made of a nitride or carbonitride containing 50 atomic % or more and 70 atomic % or less of aluminum (Al), 20 atomic % or more and 50 atomic % or less of chromium (Cr), and 4 atomic % or more and 15 atomic % or less of silicon (Si) relative to a total amount of metals including metalloids, and the atomic ratio (atomic %) A of the metal elements including metalloids and the atomic ratio (atomic %) B of nitrogen are 1.07 or less when the total of the metal elements including metalloids and the nonmetal elements is taken as 100 atomic %.
[0006] (2) In paragraph (1), 1.1 (3) In (1) or (2), it is preferable that, when observing the surface or cross section of the hard coating, there are 5 or less droplets with an equivalent circle diameter of 3 μm or more within an area of 50 μm×40 μm. (4) In any one of (1) to (3), the hard coating preferably has a compressive residual stress of 1.0 GPa or more and 4.0 GPa or less. (5) In any one of (1) to (4), an intermediate coating may be provided between the hard coating and the substrate. (6) In any one of (1) to (5), an upper layer may be provided on the hard coating. (7) In (6), the upper layer is preferably a nitride or a carbonitride. In (8) and (7), the upper layer is preferably a nitride or carbonitride containing 60 atomic % or more and 95 atomic % or less of titanium (Ti) and 5 atomic % or more and 40 atomic % or less of silicon (Si) relative to the total amount of metals including metalloids. Effect of the Invention
[0007] According to the present invention, it is possible to provide a coated cutting tool having excellent durability. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a view showing a selected area diffraction pattern of the hard coating according to the present embodiment. [Diagram 2] FIG. 2 is a diagram showing an intensity profile obtained from the selected area diffraction pattern of FIG. 1. [Diagram 3] 2 is an example of a photograph (magnification 2,000) showing the surface of the hard coating according to the present embodiment. [Figure 4] 1 is an example of a surface observation photograph (×2,000) of a hard coating according to a conventional example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The inventors of the present invention discovered that AlCrSi nitrides with a high Si content exhibit excellent durability even when the nitrogen content is high by further reducing the amount of hexagonal AlN contained at the micro level. The details of this embodiment are described below.
[0010] Hereinafter, the details of the embodiment of the present invention will be described. The coated cutting tool of this embodiment is a coated cutting tool having a hard coating made of an AlCrSi nitride or carbonitride on the surface of the tool.
[0011] The component composition, structure, characteristics, and manufacturing method of the hard coating that constitutes the coated cutting tool of this embodiment will be described in detail below.
[0012] <Composition: Aluminum (Al), Chromium (Cr), Silicon (Si)> The hard coating according to this embodiment is made of a nitride or carbonitride containing 50 atomic % or more and 70 atomic % or less of aluminum (Al), 20 atomic % or more and 50 atomic % or less of chromium (Cr), and 4 atomic % or more and 15 atomic % or less of silicon (Si) relative to the total amount of metal elements including metalloids (hereinafter referred to as metal elements). AlCrSi nitrides or carbonitrides are film species with excellent wear resistance and heat resistance. Al is an element that imparts heat resistance to the hard coating. When the hard coating contains a certain amount of Al, the heat resistance is increased. In addition, an oxidation protective coating is easily formed on the tool surface, which makes it easier to suppress tool damage. In addition, the coating structure becomes fine, which makes it easier to suppress wear of the hard coating due to welding. In addition, the cutting resistance tends to decrease. In order to fully exert these effects of adding Al, the hard coating according to this embodiment contains Al at 50 atomic % or more. It is more preferable that the Al content is 55 atomic % or more. On the other hand, if the Al content is too high, the hexagonal AlN increases and the hard coating becomes brittle. Therefore, the hard coating according to this embodiment contains Al at 70 atomic % or less. It is more preferable that the Al content is 68 atomic % or less.
[0013] Cr is an element that imparts wear resistance to the hard coating. When the hard coating contains a certain amount of Cr, the wear resistance is increased. The hard coating according to this embodiment contains 30 atomic % or more of Cr. It is more preferable that the Cr content be 35 atomic % or more. On the other hand, if the Cr content is too high, the heat resistance of the hard coating decreases. Therefore, the hard coating according to this embodiment contains 50 atomic % or less of Cr. It is more preferable that the Cr content be 45 atomic % or less. In the hard coating according to this embodiment, the total content of Al and Cr is preferably 85 atomic % or more, and more preferably 90 atomic % or more.
[0014] Silicon is an element that refines the structure of the hard coating. Refining the coating structure improves wear resistance and heat resistance. The hard coating according to this embodiment contains 4 atomic % or more of silicon. More preferably, the silicon content is 5 atomic % or more. On the other hand, if the silicon content is too high, the amount of hexagonal AlN increases, reducing the durability of the coated cutting tool. Therefore, the hard coating according to this embodiment contains 15 atomic % or less of silicon. More preferably, the silicon content is 12 atomic % or less.
[0015] The content ratio of the metal element in the hard coating according to the present embodiment can be measured by using an electron probe microanalyzer (EPMA) for the mirror-finished hard coating. In this case, for example, after mirror-finishing the hard coating surface, five analysis points with a diameter of about 1 μm are analyzed, and the content ratio can be calculated by averaging the three points excluding the maximum and minimum values.
[0016] <Atomic ratio of metal element A and atomic ratio of nitrogen B> In the hard coating according to the present embodiment, the atomic ratio A of the metal elements including metalloids and the atomic ratio B of nitrogen are 1.07 when the total of the metal elements including metalloids and the nonmetal elements is 100 atomic %.
[0017] <Crystal structure> In the hard coating according to this embodiment, the peak intensity due to the (200) or (111) plane of the cubic crystal shows the maximum intensity in the intensity profile obtained from the X-ray diffraction pattern or the selected area diffraction pattern of a transmission electron microscope. In addition, the intensity profile obtained from the selected area diffraction pattern does not have a peak mainly due to the hexagonal crystal. As a result, the amount of brittle hexagonal crystal AlN contained in the hard coating is extremely small, and it is presumed that the coated cutting tool has excellent durability even if the nitrogen contained in the hard coating is so high that the B / A ratio exceeds 1.07. The intensity profile obtained from the selected area diffraction pattern is an intensity profile with the horizontal axis being the distance (radius r) from the center of the (000) plane spot, and the vertical axis being the integrated intensity (arbitrary unit) for one circumference at each radius r. In the intensity profile obtained from the selected area diffraction pattern, a peak mainly composed of hexagonal crystals appears in the range of 3 to 4 nm from the (000) spot center. In this embodiment, "having no peak mainly composed of hexagonal crystals" means that there is no peak with a higher intensity than those before and after in the range of 3 to 4 nm from the spot center. In this embodiment, the intensity profile obtained from the selected area diffraction pattern is evaluated after removing the background. Even if the diffraction pattern of hexagonal AlN is confirmed in the selected area diffraction pattern, if the amount is very small, no peak (apex) will appear in the intensity profile, and it will only swell slightly.
[0018] Within the range that satisfies the above-mentioned requirements, the hard coating according to this embodiment may contain metal elements other than Al, Cr, and Si. For example, in order to improve the wear resistance, heat resistance, lubricity, etc. of the hard coating, it may contain one or more elements selected from elements of Groups 4a, 5a, and 6a of the periodic table, and B, Y, and Cu. These elements are generally added to AlTiN-based and AlCrN-based hard coatings to improve the properties of the hard coating, and as long as the content ratio is not excessive, the durability of the coated cutting tool will not be significantly reduced. When the hard coating according to this embodiment contains metal elements other than Al, Cr, and Si, the total content ratio is preferably 10 atomic % or less. More preferably, it is 5 atomic % or less.
[0019] In the hard coating according to this embodiment, it is preferable that there are 5 or less droplets having a circle equivalent diameter of 3 μm or more within an area of 50 μm×40 μm when observed on the surface or cross section. More preferably, there are 2 or less droplets. In the present invention, droplets refer to deposits on the hard coating caused by molten particles of about 1 to several tens of μm that fly out from the cathode in the arc ion plating method. The durability of the tool is increased by having fewer coarse droplets in the hard coating. Furthermore, it is preferable that there is 1 or less droplets having a circle equivalent diameter of 5 μm or more within an area of 50 μm×40 μm when observed on the surface or cross section of the hard coating according to this embodiment. The durability of the tool is increased by having fewer coarse droplets. The droplets of the hard film may be determined by observing five or more fields of view of a 50 μm×40 μm area under an electron microscope at a magnification of 2000 times and averaging the results.
[0020] The hard coating according to this embodiment preferably has a residual compressive stress of 1.0 GPa or more and 4.0 GPa or less. A residual compressive stress of 1.0 GPa or more and 4.0 GPa or less is preferable because peeling of the coating is less likely to occur.
[0021] The coated cutting tool of this embodiment may have an intermediate coating between the substrate and the hard coating, if necessary. For example, a nitride, carbonitride, or carbide containing one or more elements selected from titanium (Ti), aluminum (Al), and chromium (Cr) may be provided. A modified layer may also be provided by metal bombardment. An upper layer may also be provided on the hard coating to increase the durability of the coated cutting tool. The upper layer is preferably a nitride or carbonitride. The upper layer is preferably a nitride or carbonitride containing 60 atomic % to 95 atomic % titanium (Ti) and 5 atomic % to 40 atomic % silicon (Si).
[0022] The hard coating of this embodiment is a physical vapor deposition coating. The hard coating of this embodiment is preferably a hard coating coated by an arc ion plating method, which has excellent adhesion among physical vapor deposition coatings. A hard coating containing a large amount of Al is likely to generate a large amount of droplets. Although the hard coating is a high-Al coating produced by the arc ion plating method, the tool performance of the coated cutting tool is likely to be stable by reducing the number of coarse droplets. The coated cutting tool according to the present embodiment is preferably coated using a film-forming device that has permanent magnets on the back and outer periphery of the target, and further includes a cathode provided in front of the target with a magnetic field generating coil that generates a magnetic field for pushing plasma forward. In addition, the distance from the target surface to the substrate is preferably 250 mm or more. The longer the distance from the target surface to the substrate, the fewer the coarse droplets that reach the substrate. The coating temperature is preferably 450° C. to 550° C. The negative bias voltage applied to the substrate is preferably −180 to −120 V. The pressure inside the furnace is preferably 2 to 8 Pa. The current input to the target is preferably 100 to 200 A. The current input to the magnetic field generating coil is preferably 3 to 10 A. EXAMPLES
[0023] <Base material> As the base material, a two-flute ball end mill made of cemented carbide with a composition of WC(bal.)-Co(8 mass%)-Cr(0.5 mass%)-VC(0.3 mass%), an average WC particle size of 0.6 μm, and a hardness of 93.9 HRA was prepared. Also, a test piece made of cemented carbide was prepared for residual stress measurement.
[0024] <Manufacturing method> For film formation, a film formation apparatus using the arc ion plating method was used. This apparatus includes a plurality of cathodes (arc evaporation sources), a vacuum chamber, and a base material rotation mechanism. The apparatus used for the coating in this example is equipped with a cathode in which permanent magnets are arranged on the back and outer periphery of the target, and a magnetic field generation coil for generating a magnetic field for pushing the plasma forward is provided in front of the target. Also, the distance from the target surface to the base material is 400 mm. The inside of the vacuum chamber is evacuated by a vacuum pump, and gas is introduced from the supply port. A bias power supply is connected to the base material installed in the vacuum chamber, and a negative bias voltage is independently applied to the base material. The base material rotation mechanism has a work table, a plate-shaped jig on the work table, and a pipe-shaped jig on the plate-shaped jig attached. The work table rotates at a speed of 3 revolutions per minute, and the plate-shaped jig and the pipe-shaped jig rotate and revolve respectively.
[0025] <Heating and vacuum evacuation process> The base materials were fixed to the pipe-shaped jigs in the vacuum chamber respectively, and the pre-film formation process was carried out as follows. First, the inside of the vacuum chamber was evacuated to 5×10Pa or less. Then, the base materials were heated by heaters installed in the vacuum chamber until the base material temperature reached 500°C, and vacuum evacuation was performed. As a result, the base material temperature was set to 500°C, and the pressure inside the vacuum chamber was set to 5×10 -3 Pa or less.
[0026] <Ar bombardment process> Thereafter, Ar gas was introduced into the vacuum chamber, and the pressure inside the chamber was set to 0.50 Pa. Thereafter, a current of 20 A was supplied to the filament electrode, and a negative bias voltage of −150 V was applied to the substrate, and Ar bombardment was carried out for 60 minutes.
[0027] <Film forming process> After Ar bombardment, the gas in the vacuum chamber was replaced with nitrogen, and the pressure in the vacuum chamber was set to 4 Pa. A current of 100 A was supplied to the Al60Cr30Si10 target (numbers are atomic ratios; the same applies below), a current of 5 A was supplied to the magnetic field generating coil, and a bias voltage of -150 V was applied to the substrate to coat a hard nitride film with a thickness of approximately 2 μm. Next, a current of 150 A was supplied to the Ti75Si25 target, a current of 5 A was supplied to the magnetic field generating coil, and a bias voltage of -50 V was applied to the substrate to coat an upper layer of nitride with a thickness of approximately 1 μm.
[0028] In the conventional coating, a deposition apparatus equipped with a cathode with permanent magnets on the back and outer periphery of the target was used. The distance from the target surface to the substrate was 170 mm. The deposition conditions were the same as those of the coating of this embodiment, except that no current was input to the magnetic field generating coil. The hard coating of the conventional example corresponds to Patent No. 6410797.
[0029] ≪Composition analysis≫ The film composition was measured using a wavelength dispersive electron probe microanalysis (WDS-EPMA) attached to an electron probe microanalyzer (JXA-8500F, manufactured by JEOL Ltd.). A ball end mill for evaluating physical properties was mirror-finished and the accelerating voltage was 10 kV and the probe current was 5 × 10 -8 A, The acquisition time was 10 seconds, and the analysis area was an area of approximately 1 μm in diameter, with five points measured, and the average value was calculated. The average composition of the hard coatings according to this embodiment and the conventional example was (Al56Cr33Si11)N. Also, the B / A ratio of this embodiment was 1.20.
[0030] ≪TEM analysis≫ Microanalysis was performed using a field discharge transmission electron microscope (JEM-2100F manufactured by JEOL Ltd.). The selected-area diffraction pattern of the hard coating was obtained with an accelerating voltage of 200 kV, a selected-area region of φ500 nm, a camera length of 100 cm, and an incident electron dose of 5.0 pA / cm. 2 The results were obtained under the conditions of (on a fluorescent screen). The central part of the AlCrSi nitride hard coating in the thickness growth direction was analyzed. The brightness of the obtained selected area diffraction pattern was converted to obtain an intensity profile.
[0031] <Residual stress> Residual stress and crystal structure were measured using an X-ray diffraction device. 2 Measured by the ψ method. The compressive residual stress in this example and the comparative example was about 3 GPa.
[0032] (Condition) Dry processing Tool: 2-blade carbide ball end mill Model number: EPDBE2010-6, ball radius 0.5mm Cutting method: bottom cutting Work material: STAVAX (52HRC) (manufactured by BOHER-Uddeholm Co., Ltd.) Cut: Axial, 0.04mm, Radial, 0.04mm Cutting speed: 75.4m / min Feed per blade: 0.0179mm / blade Cutting distance: 15m Evaluation method: After cutting, the material was observed at a magnification of 1000x using a scanning electron microscope, and the width of the abrasion between the tool and the workpiece on the tool flank was measured. The part with the largest abrasion width was recorded as the maximum wear width on the flank.
[0033] [Table 1]
[0034] In this embodiment, the maximum wear width is smaller than that of the conventional example. FIG. 1 shows the selected area diffraction pattern of the hard coating according to this embodiment. FIG. 2 shows the intensity profile of the selected area diffraction pattern obtained from FIG. 1. Peak "2" in FIG. 2 is the peak intensity corresponding to the (111) plane of the cubic crystal, peak "3" is the peak intensity corresponding to the (200) plane of the cubic crystal, and peak "4" is the peak intensity corresponding to the (220) plane of the cubic crystal. Peak "1" has a slight bulge, but does not have sharp peaks like peaks "2" to "4". In other words, the hard coating of this embodiment does not have peaks mainly composed of hexagonal crystals. It is confirmed that this embodiment contains a small amount of hexagonal AlN. In this embodiment, the amount of hexagonal AlN at the micro level is extremely small, and it is presumed that the durability was superior to that of the conventional example even though the nitrogen content of the hard coating was high.
[0035] Figure 3 shows an example of a surface observation photograph of the coated cutting tool of this embodiment. Figure 4 shows an example of a surface observation photograph of a conventional coated cutting tool. It can be seen that this embodiment has fewer coarse droplets than the conventional example. Depending on the tool shape and processing conditions, droplets can have a significant effect on tool performance. The coated cutting tool of this embodiment is suitable for smaller diameter tools. By applying the hard coating of this embodiment to small diameter tools that are more susceptible to droplets, it is expected that durability will be further improved compared to the conventional example.
Claims
1. A coated cutting tool having a substrate and a hard coating on the substrate, the hard coating is made of a nitride or a carbonitride containing, relative to a total amount of metals including metalloids, 50 atomic % or more and 70 atomic % or less of aluminum (Al), 20 atomic % or more and 50 atomic % or less of chromium (Cr), and 4 atomic % or more and 15 atomic % or less of silicon (Si); and the atomic ratio (atomic %) A of the metal elements including metalloids and the atomic ratio (atomic %) B of nitrogen, when the sum of the metal elements including metalloids and the non-metal elements is taken as 100 atomic %, satisfies the relationship of 1.07<B / A<1.30; in an intensity profile obtained from an X-ray diffraction pattern or a selected-area diffraction pattern of a transmission electron microscope, the peak intensity due to the (200) plane or the (111) plane of a cubic crystal shows the maximum intensity, and the intensity profile obtained from the selected-area diffraction pattern does not have a peak mainly due to a hexagonal crystal.
2. 2. The coated cutting tool according to claim 1, characterized in that 1.1<B / A<1.
25.
3. 3. The coated cutting tool according to claim 1, wherein, when the surface or cross section of the hard coating is observed, there are 5 or less droplets having an equivalent circle diameter of 3 μm or more within an area of 50 μm×40 μm.
4. 2. The coated cutting tool according to claim 1, wherein the hard coating has a compressive residual stress of 1.0 GPa or more and 5.0 GPa or less.
5. 2. The coated cutting tool according to claim 1, further comprising an intermediate coating between the hard coating and the substrate.
6. 2. The coated cutting tool according to claim 1, further comprising an upper layer provided on the hard coating.
7. The coated cutting tool of claim 6, wherein the overcoat is a nitride or a carbonitride.
8. 8. The coated cutting tool according to claim 7, wherein the upper layer is a nitride or carbonitride containing 60 atomic % or more and 95 atomic % or less of titanium (Ti) and 5 atomic % or more and 40 atomic % or less of silicon (Si) with respect to a total amount of metals including metalloids.
Citation Information
Patent Citations
Coated cutting tool and method for producing same
WO2015141743A1
Cited By
Cutting tools
JP7938261B1
Coated cutting tool
WO2026181733A1